PENGUATAN NILAI AKHLAKUL KARIMAH MELALUI PENGAJIAN REMAJA DI DESA MENAMPU, KECAMATAN GUMUKMAS - Ulum, M Bustanul; Fadholi, Amak; Dasuki, Mohammad; Yaqin, Ainul; Hori, Muhammad (Universitas Al-Falah As-Sunniyah Kencong Jember, 2025)
Recitation is a non-formal educational activity carried out in a place of worship in an Islamic society as a forum for deep understanding of religion, both the material conveyed is, ahlak, fiqh, worship and muamalah, while the material presented at the recitation of adolescents in Menampu village is more specifically on the morality which aims to shape the morality of teenagers which is increasingly deteriorating. In this program the authors use the mentoring method, step by step mentoring stages. the results of this program have an impact on society and have an impact on science, the impact on society: the community fully supports the implementation of these activities and is ready to fortify adolescents from negative influences, the community is more aware of the abilities of adolescents, the community is educated with youth activities, and also the community motivated by these activities. Scientific impact: the increasing religious insights of adolescents about religious ideas that are beneficial both for themselves and for others, and make them more active, committed, have a strong stance that is not easily influenced by negative things. the discussion is the issue and focus of empowerment, the purpose of the reasons for choosing assistance, the conditions for choosing the assisted subject, the expected output of assistance, the dissemination is that in the first stage I went to assistance to be invited to participate in religious activities, in the second stage I with the village cleric had deliberation in choosing a suitable method and easy to understand for assistance in delivering material, in the third stage, namely determining the place, in this third stage we chose mosques and prayer rooms, because mosques and prayer rooms are sacred places. Islam upholds science in the Koran, it is often called upon so that people want to think and cultivate the abilities of reason, so it is therefore very suitable if mosques and prayer rooms are made into majlis of science. Keywords: recitation, of youth, morality